Kedukaan Pandemi Covid-19 Menentang Prinsip Konseling Pastoral di Tengah Tema Reposisi Pekabaran Injil HKBP Tahun 2020 - Sinaga, Lamria (Sekolah Tinggi Diakones HKBP, 2021)
This article describes the debilitating grief situation of the entire community due to the Covid-19 pandemic. This grief causes heartbreak the requires guidance of pastoral counseling. This grief occurred because of the outbreak of the Covid-19 virus which obliged every community to do social/physical distancing, social resitrictions even lockdown. On the other hand, churches that are midst of the community have the responsibility to response and change that have occurred due to the Covid-19 pandemic. In 2020, HKBP set as the year repositioning the gospel, so HKBP needs to change its approach how to serve congregation/community. The method used to answer the problems posed in this paper is literature review by utilizing printed book sources, international websites and other articles related to the Covid-19 pandemi